The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1080/014850100262281
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity of Mouse Sperm Was Not Affected by Low Doses of Aspirin-Like Drugs

Abstract: To investigate some possible effects of low doses of nonsteroidal anti-inflammatory drugs upon functional activity of mouse sperm, the authors injected lysine acetyl salicylate (im 14.3 mg/kg day(-1), ibuprofen (ip 5.6 mg/kg day(-1)), or piroxicam (ip 0.28 mg/kg day(-1) to pregnant females (the male cohort was sacrificed at adulthood) (A) or to adult males during 35 (B) or 60 (C) days. Parameters measured were motility, viability, acrosomal integrity, responses to hypoosmotic shock, in vitro fertilization inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…Similar effects on gonad development and reproductive health of F0 adult female rodents have been described after exposure to high doses of APAP or indomethacin (26,27). However, fertility of adult male rats (26) and sperm parameters in mice (25) were not altered by exposure in utero to these drugs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similar effects on gonad development and reproductive health of F0 adult female rodents have been described after exposure to high doses of APAP or indomethacin (26,27). However, fertility of adult male rats (26) and sperm parameters in mice (25) were not altered by exposure in utero to these drugs.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, in adult rats, long-term treatment with APAP at high doses impairs sexual competence, sperm count and quality, and fertility (24). Conversely, adult mouse sperm parameters are not affected after in utero exposure to low doses of ASA or IBU (25). Similarly, in vivo administration of APAP or indomethacin to pregnant rats during embryogenesis decreases the number of fetal germ cells and accelerates their embryonic differentiation but does not affect the fertility of adult male rats (26).…”
mentioning
confidence: 99%
“…Though, in contrast, only one animal study conducted on rams showed improvement in sperm motility after aspirin supplementation at 75 mg/kg, for 4 days, however, in this study other sperm markers such as count and volume were negatively affected (Tanyildizi & Bozkurt, 2003). Alternatively, there was a blunted effect on sperm motility and viability after administration of aspirin at 14.3 mg kg −1 day −1 , for 35 and 60 days, in adult mouse males (Stutz et al, 2000).…”
Section: Ta B L Econtrasting
confidence: 80%
“…The present study represents the first GC/MS-MS global analysis of fetal testicular steroidogenesis demonstrating that, in addition to suppression of testosterone, the effect of ibuprofen on the expression of CYP17A1 also negatively impacted androstenedione and to a greater extent 5α-DHT. Further supporting evidence for ibuprofen being an anti-androgenic compound is the observation that low doses of this NSAID (5–6 mg/kg/day for 35 days) inhibited plasma levels of testosterone in adult male mice59. Ibuprofen has also been shown to inhibit the human UDP-glucuronosyltransferases UGT2B15 and UGT2B17, and the latter is very important for glucuronidation and testosterone excretion60.…”
Section: Discussionmentioning
confidence: 96%